施密特平行轴联轴器扭振特性分析 - 杜雪松; 王孟; 朱才朝 (Jixie chuandong)
Schmidt offset coupling is a coupling,it is suitable for connecting two parallel axis which have large partial distance.The dynamic performance of the transmission system has great influence on the quality of the transmission,but there is still lack of effective methods of the coupling dynamic characteristic analysis.Through coupling the input,output components and Schmit offset coupling,a dynamic model analysis model of the system is established and dynamical equations of transmission system are built based on energy method.The natural characteristics and the dynamic response analysis of torsional vibration model of this drive system are carried out.The results show that the proposed method has simplicity and universal,it can analyze and predict drive system dynamic characteristics in the design phase.